Development of a Website-Based Education Management Information System in Inclusive Schools - Siti Nuraini Purnamawati; Rita Aryani; Indina Tarjiah; Erfan Kurniawan (Universitas Pendidikan Ganesha, 2022)
One of problems in inclusive schools is caused by there is no inclusive school management information system. Based on these problems, it is necessary to have a management information system in inclusive schools that can help schools, the government and the community to create inclusive schools that can be accessed by everyone. This study aims to produce a product from the development of a website-based education management information system in inclusive schools. The research method used in this research is Research and Development (RnD) with the Borg and Gall model at stages four to ten. The process starting from the stages of data collection, planning, development, stage I expert validation, stage I expert revision, stage II expert validation, stage II expert revision. Product trials in inclusive schools, revisions to product trials in inclusive schools, and the final product of an education management information system in inclusive schools. The subject of this study involving inclusive schools parties such as teachers, and school committees from parents and some expert. The results of this study can be concluded that the development of a website-based education management information system in this inclusive school has been successfully carried out based on the Borg and Gall development model. The development of a website-based education management information system in this inclusive school has also obtained a very good eligibility level. So that it can be used by inclusive schools in managing education to provide the information needed by the community, government, and the school.